Coralligenous cliffs: distribution and extent along the Tuscany coasts and spatial variability of the associated assemblages - PIAZZI, LUIGI; CECCHI, ENRICO; CINTI, MARIA FRANCESCA; MARINO, GIACOMO; NICASTRO, ANDREA; PACCIARDI, LORENZO; PERTUSATI, MARCO; RIA, MICHELA; DE BIASI, ANNA MARIA (Mediterranean Marine Science, 2023)
Coralligenous reefs are the main biogenic constructions of the Mediterranean Sea. The two main coralligenous morphologies are cliffs and platforms. Coralligenous cliffs mostly develop in shallower waters (about 20-50 m) on vertical/sub vertical rocky substrates. Coralligenous platforms are mostly distributed on horizontal substrates below 40-50 m depth on detritic bottoms and rocky outcrops of the continental shelf. The present study aims at contributing to the knowledge of coralligenous cliffs through the assessment of their distribution and extent in a wide geographic zone of northwestern Mediterranean Sea, focusing on the structure and the spatial variability of the associated assemblages. To achieve these objectives, coralligenous cliffs of Tuscany coasts were mapped through Multibeam and Remotely Operated Vehicles. The area of coralligenous cliffs was also manually calculated for each study site using linear extent and bathymetric range of the habitat. In addition, the structure of the associated assemblages was investigated by a multifactorial sampling design taking into account spatial scales ranging from meters to tens of kilometres. Coralligenous cliffs were present in all the study sites, with a linear extent of about 20% of Tuscany’s rocky coastline and an area of about 20% of the Tuscan coralligenous reefs. The difference between data manually calculated and those obtained by Quantum- GIS software was about 33% of the total area. A continental-to-island gradient and a latitudinal gradient were the main factors driving the structure of the associated assemblages. Results highlighted that coralligenous cliffs represent a considerable part of circalittoral biogenic habitat, suggesting that their relevance may be greater than what normally emerges from seabed mapping and that they should be considered separately in monitoring programs, impact assessment studies and management plans.